Assessing Atmospheric Response to Surface Forcing in the Observations. Part I: Cross Validation of Annual Response Using GEFA, LIM, and FDT - Liu, Zhengyu; Wen, Na; Fan, Lei (Journal of Climate, 2012)
Three statistic methods [generalized equilibrium feedback analysis (GEFA), linear inverse modeling (LIM), and fluctuation-dissipation theorem (FDT)] are compared for their assessment of the atmospheric response to sea surface temperature variability in the coupled climate system with a sample length comparable with the observations (decades). The comparison is made first in an idealized coupled model and then in the observations. For daily to pentad data, for a linear stochastic system, the simple model study demonstrates that all three methods are able to provide a consistent assessment of the atmospheric response. For monthly data, GEFA is able to produce an assessment comparable with the daily or pentad assessments using the three methods. The consistence of the three methods is further confirmed in the observations for the responses of the atmospheric geopotential height (at 200 hPa) to the tropical ENSO mode and the North Pacific mode. It is found that the three methods produce a consistent response with the overall pattern correlation over 0.95 and the amplitude difference within 10%-20%. The consistent results in both the simplemodel and the observations suggest that the three statistical methods can be used as a cross validation on the robustness of the assessment of the atmospheric response to surface forcing in the observations. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000309653800022&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Meteorology & Atmospheric Sciences SCI(E) EI 6 ARTICLE 19 6796-6816 25